2022
DOI: 10.3389/fnins.2022.882602
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the autonomic nervous system by one session of spinal low-level laser therapy in patients with chronic colonic motility dysfunction

Abstract: Patients with a defecation disorder may not evoke a normal defecation reflex, or the reflex may be excessive, as a dysfunction of the spinal autonomic nervous system. Treatment with various forms of lumbar and sacral neuromodulation have shown symptom improvement, but potential changes in autonomic functioning are rarely studied. Here we evaluate the effects on autonomic function of a single session of low-level laser therapy (LLLT) on the lumbar and sacral spine in 41 patients with chronic gastrointestinal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The vagus nerve supplies the upper part of the tract from the esophagus to the small intestine, while the sacral nerves supply the lower part from the colon to the anus. When stimulated, the parasympathetic system causes smooth muscle contraction, promotes peristalsis, stimulates glandular secretion, enhances intestinal secretions, increases blood flow, and relaxes the internal anal sphincter, all essential for proper gastrointestinal function[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vagus nerve supplies the upper part of the tract from the esophagus to the small intestine, while the sacral nerves supply the lower part from the colon to the anus. When stimulated, the parasympathetic system causes smooth muscle contraction, promotes peristalsis, stimulates glandular secretion, enhances intestinal secretions, increases blood flow, and relaxes the internal anal sphincter, all essential for proper gastrointestinal function[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system (CNS) provides its inputs to the gastrointestinal tract via the autonomic nervous system (ANS), which plays a key role in controlling the energy homeostasis and body weight, by modulating the sympathetic and parasympathetic (or vagal) tone [15], [16], [17]. It has been well reported that the autonomic function altered from the fasting state to the postprandial state [18].…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) has been used as a noninvasive method to assess autonomic nervous system activity due to its simplicity, accuracy and reproducibility. Several time domain, frequency domain and non-linear methods have been developed to record sympathetic and parasympathetic activities from the HRV signal that is derived from the electrocardiogram (ECG) [7], [19], [21], [22]. Different time domain, frequency domain and/or nonlinear HRV parameters can be calculated from the HRV signal, which can be used to train an artificial neural network (ANN).…”
Section: Introductionmentioning
confidence: 99%